ANALISIS PENGUKURAN KINERJA BALANCED SCORECARD PADA PDAM MAJA TIRTA KOTA MOJOKERTO - CHETISA PUTRI, KHANSA (Jurnal Akuntansi AKUNESA, 2018)
This research is aimed to find out the performance of PDAM Maja Tirta by using Balanced Scorecard to measure the performance of the company. The type of this research is quantitative using primary data and secondary data. Data collection methods were obtained from interviews, questionnaires distribution, documentation, and direct observation. While data analysis included financial percpective using gpm, total cost, roe, roa, current ratio, leverage, and npm; customers percpective using customer satisfaction index, internal business processes using innovation, operation, and after sales service; also learning and growth using employee satisfaction index. Test statistic shows that data in this research is valid and reliable. Based on the result also shows that for both internal business process and learning and growth perspective is sufficient. While customer perspective is great and financial perspective is very poor. Keywords: balanced scorecard, performance, measurement